2017
DOI: 10.1007/s10661-017-5936-0
|View full text |Cite
|
Sign up to set email alerts
|

Microphytobenthic biomass, species composition and environmental gradients in the mangrove intertidal region of the Andaman Archipelago, India

Abstract: Monthly sampling in mangrove intertidal sediments of Andaman Archipelago was carried out during a 1-year study (January to December, 2013) in order to analyse the spatial and temporal distribution of microphytobenthos (MPB) and MPB biomass (sediment chlorophyll-a (chl-a)) in the surficial layer 0-1 cm. The MPB community was mainly composed of diatoms. The MPB biomass concentration in surface sediment (0-1 cm) ranged from 0.7 to 16.98 μg cm. Population density of benthic diatoms varied from 78 to 224 ind cm. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
2
4
0
Order By: Relevance
“…The significant relationship between sediment Chl a concentration and diatom density in this study suggested the diatoms as an important component of the microphytobenthos community. This was consistent with other findings that the diatoms were the most important component of the microphytobenthos assemblages of estuarine mudflats and mangroves (McLusky ; Thornton et al ; Balasubramaniam et al ). The Nitzschia and Gyrosigma genera represented the majority of diatoms in the microalgal film in winter, while Nitzschia and Coscinodiscus were the dominant genera of the mangrove microalgae film in spring in this study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The significant relationship between sediment Chl a concentration and diatom density in this study suggested the diatoms as an important component of the microphytobenthos community. This was consistent with other findings that the diatoms were the most important component of the microphytobenthos assemblages of estuarine mudflats and mangroves (McLusky ; Thornton et al ; Balasubramaniam et al ). The Nitzschia and Gyrosigma genera represented the majority of diatoms in the microalgal film in winter, while Nitzschia and Coscinodiscus were the dominant genera of the mangrove microalgae film in spring in this study.…”
Section: Discussionsupporting
confidence: 93%
“…The range of Chl a concentration in the cold seasons, 0.61–4.74 μ g cm −2 , in this study fell within the ranges reported in other intertidal areas (Pinckney et al ; Liu et al ; Balasubramaniam et al ). The significant relationship between sediment Chl a concentration and diatom density in this study suggested the diatoms as an important component of the microphytobenthos community.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Some can protect themselves physiologically against the damaging effects of exposure (Blanchard et al, 2004;Perkins et al, 2010) by dissipating the excess energy absorbed by light-harvesting centers, a process S. Salleh and A. McMinn: Impact of irradiance and temperature on microphytobenthos known as non-photochemical quenching (NPQ), while others can move vertically in the sediment, adjusting their position to minimize irradiance (Consalvey et al, 2004a;Perkins et al, 2010;Cartaxana et al, 2013). For instance, in a study by Mouget et al (2008) it was shown that benthic diatoms with a high migratory capacity could experience high photosynthetic activity without any evidence of photodamage, while non-migratory taxa showed a significant depression in photosynthetic activity, which was caused by high irradiance and/or UV-B.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, benthic diatoms inhabiting sediment surfaces in estuaries are usually able to recover from extreme temperatures and light photoinhibition caused by tidal changes, since photoinhibition is only rarely recorded in these communities (Defew et al, 2004;Lee and McMinn, 2013;Perkins et al, 2006). Furthermore, many have the ability to migrate vertically, hence positioning themselves within the sediment at a depth that provides shading from excess irradiance and provides an optimal light environment for their photosynthetic activities (Cartaxana et al, 2011;Mouget et al, 2008;Perkins et al, 2010).…”
Section: Introductionmentioning
confidence: 99%